Stylistic devices for teenager character sketch creation in the Guilty Stars novel - Leila M. Mukhtarova, Flera G. Mukhametzyanova, Elena A. Venidiktova,; Litvina, Lilia M. (Opción, 2019)
This article examines the analysis of the novel The Guilty Stars in the context of the literary genre young adult literature presented in the graduate student work via the theoretical and linguistic analysis of the specified novel. Raising the themes of love, friendship, family as the important aspects of a teenager’s life, the author shows the self-irony of adolescents over their own tragic fate. In conclusion, the most used literary trails are the metaphor and artistic comparison, along with them the author skillfully includes vulgarisms, Americanisms and colloquial expressions in the dialogues of adolescents.